Effect of isolated fatty acids from flaxseeds Linumusitatissimum against LeishmaniatropicaIn vitro. - Mohammed Hasan, Hasan (International Journal of Psychosocial Rehabilitation, 2021)
The current study aimed to test the effectiveness of Fatty acid separationfrom the seeds of the flax plant Linum usitatissimum on the parasiteLeishmaniatropica. Palmatic acid, Steric acid, Olic acid, and Arachidic acidBehenic acid). These fatty acids were used as a possible anti-inflammatoryagents in vitro, as the results showed that the concentration of 100 μg/mlgave a complete inhibition of the parasite’s growth in the promastigote formin 48 hours and up by 100% compared to the control group, whichgrowth of the parasite was witnessed at all times, while the concentration of25 μg/ml showed a decrease in the percentage of inhibition compared to therest of the concentrations, which was 78.8% at the time of 96 hours, and theinhibitory concentration for 90% of the parasites (LC90) was at theconcentration of 50 μg/ml. milliliters at log phase 96 hours of culture. Thisled to a reduction in the number of generations and an increase in the timerequired to produce them compared to the control group.